The Influence Current Ratio, Return on Equity and Debt to Equity Ratio toward Price Book Value - Nazma alaika silma; Anita Handayani (INNOVATION RESEARCH JOURNAL, 2023)
The purpose of this study was to determine and analyze the effect of Current Ratio, Return on Equity and Debt to Equity Ratio on Price to Book Value in service companies in the Hotel, Restaurant and Tourism sub-sector which are listed on the Indonesia Stock Exchange for the 2017- 2021 period. This study uses the theory of Financial Management related to the current ratio, Return On Equity debt to equity ratio and Price to Book Value. The approach used in this study is to use an associative approach and the type of data used is quantitative. The population in this study were 49 service companies in the hotel, restaurant and tourism sub-sector. The number of samples is 13 service companies in the Hotel, Restaurant and Tourism sub-sector using pure positive sampling technique. The data analysis method used multiple linear regression analysis techniques, with the SPSS 27.0 application tool. The results showed that the current ratio has a negative and insignificant effect on Price to Book Value, Return on Equity has a positive and significant effect on Price to Book Value and the Debt to equity ratio has a negative and insignificant effect on Price to Book Value, in Service companies in the Hotel, Restaurant and Tourism sub-sector which are listed on the Indonesia Stock Exchange. Keywords : Current Ratio, Return on Equity, Debt To Equity Ratio, Price to Book Value.